Fourier-based filtering approach for identification of protein- coding regions in DNA sequences - Das, Bihter; Turkoglu, Ibrahim (Institute of Electrical and Electronics Engineers Inc., 2015)
Identification of protein-coding regions is very difficult in genomic research. This coding regions have 3-base periodicity are named as exon. The aim of this paper is to estimate position of exon in the DNA sequence used filter approach based Fourier. For this purpose, DNA sequences of M8694 gene in human species are transformed to numeric sequences by EIIP mapping technique. Time frequency domain of numeric DNA sequences is obtained by Fourier method and 3-period signal is filtered using antinotch filter. Exon regions of filtered signal are defined successfully according to the specified percentile threshold. © 2015 IEEE.
DNA Dizilimlerindeki Protein Kod Bölgelerinin Tanimlanmasi için Fourier Tabanli Filtreleme Yaklaşimi
2015 23rd Signal Processing and Communications Applications Conference, SIU 2015 -- 16 May 2015 through 19 May 2015 -- Malatya -- 113052
Keywords: Antinotch filter; DNA sequence; Exon; Fourier transform